A Neonate With Vertical Transmission of COVID-19 and Acute Respiratory Failure: A Case Report. (1st December 2021) - Farmer, Meredith L.
Abstract : Background: This case describes a case of vertical transmission of COVID-19 from a mother to her neonate. The neonate subsequently developed acute respiratory failure consistent with adult symptoms of COVID-19. Clinical Findings: This preterm neonate was born at 33 4/7 weeks' gestational age to a COVID-19–positive mother and admitted to the neonatal intensive care unit (NICU) for prematurity and respiratory distress. The neonate developed acute respiratory failure with severe persistent pulmonary hypertension of newborn (PPHN) and required intubation and maximum respiratory and cardiovascular support. The neonate subsequently tested positive for COVID-19 at 24 hours of life. Primary Diagnosis: Acute respiratory failure related to COVID-19 infection. Interventions: The neonate was admitted to the NICU on CPAP. At 11 hours of life, the neonate began to exhibit signs of worsening respiratory distress requiring intubation, mechanical, and high frequency ventilation. An echocardiogram revealed severe PPHN. The neonate required dopamine to manage hypotension and was treated with steroids to decrease inflammation associated with airway edema noted during intubation. Pharmaceutically induced paralysis, analgesia, and sedation was used to manage persistent hypoxia. Outcomes: The neonate fully recovered from acute respiratory failure and was discharged home with the mother. Practice Recommendations: Newborns born to mothers who are positive for COVID-19 are at risk for vertical transmission of COVID-19 and should be monitored closely for acute respiratory failure. Respiratory medical management should include supportive care. Staff should also encourage parents to consider receiving the COVID-19 vaccine to protect their newborn from the possibility of developing acute respiratory failure.